Ketogenic Diet Impairment of Mycobacterium ulcerans Growth and Toxin Production and Enhancement of Host Response to Infection in an Experimental Mouse Model. (4th May 2021) - Foulon, Mélanie; Robbe-Saule, Marie; Esnault, Lucille; Malloci, Marine; Mery, Anthony; Saint-André, Jean-Paul; Croue, Anne; Kempf, Marie; Homedan, Chadi; Marion, Estelle; Marsollier, Laurent
Abstract: Ketogenic diets have been used to treat diverse conditions, and there is growing evidence of their benefits for tissue repair and in inflammatory disease treatment. However, their role in infectious diseases has been little studied. Buruli ulcer ( Mycobacterium ulcerans infection) is a chronic infectious disease characterized by large skin ulcerations caused by mycolactone, the major virulence factor of the bacillus. In the current study, we investigated the impact of ketogenic diet on this cutaneous disease in an experimental mouse model. This diet prevented ulceration, by modulating bacterial growth and host inflammatory response. β-hydroxybutyrate, the major ketone body produced during ketogenic diet and diffusing in tissues, impeded M. ulcerans growth and mycolactone production in vitro underlying its potential key role in infection. These results pave the way for the development of new patient management strategies involving shorter courses of treatment and improving wound healing, in line with the major objectives of the World Health Organization. Abstract : Buruli ulcer caused by Mycobacterium ulcerans results in severe skin damage. We showed that ketogenic diet can control the bacillus and decrease the host inflammatory response, thus demonstrating its potential to improve lesion healing. Graphical Abstract: